Formal mentoring, gender type in mentorship and individuals' psychosocial: A moderating model approach - Azman Ismail; Michael Khian Kho Jui; Muhammad Madi Bin Abdullah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
Formal mentoring is a type of training and development program and if mentors can properly implement the related activities, may lead to increased individuals' psychosocial. More importantly, recent studies in this area have revealed that the effect of formal mentoring on individuals' psychosocial has not been consistent if gender type played an active role in organizations. The aim of this study is, therefore, to examine the effect of formal mentoring and gender type on individuals' psychosocial based on information derived from 153 usable questionnaires administered to employees who have worked in the selected public university in Sarawak, Malaysia (SRWKUNIV). The outcomes of hierarchical regression analysis showed that interaction between same-gender and formal mentoring, and interaction between cross-gender and formal mentoring positively and significantly correlated with individuals' psychosocial. The results confirm that gender type does act as a full moderating variable in the formal mentoring model of the organizational sample. In addition, implications and discussions are elaborated.
Keywords: 330; Formal Mentoring; Gender type; Individuals' Psychosocial; Malaysia